Design Criteria in Revitalizing Old Warehouse District on the Kalimas Riverbank Area of Surabaya City - Endang Titi Sunarti Darjosanjoto; Setyo Nugroho; R.Winton Danardi (Journal of Visual Art and Design, 2015)
Neglected warehouse buildings along the Kalimas River have created a poor urban faÃ§ade in terms of visual quality. However the city government is planning to encourage tourism activities that take advantage of Kalimas River and its surrounding environment. If there is no good plan in accordance with the concept of local identity for old city of Surabaya, it will reduce it as a tourist attraction. In reference to the issue above, design criteria needs to be compiled for revitalizing the old warehouse district, which is expected to revive the identity of this district and be able to support the city's tourism. This study was conducted by recording field observations, and the data was analyzed using the character appraisal method. The character appraisal analysis method is presented in the form of street picture data, which is divided into determined segments. The results show that there are five components including place attachment, sustainable urban design, green open space design, ecological riverfront design, and activity support that should be considered in the revitalization of the warehouse district. Those components are divided into two parts: building and open space at the riverbank. There are 13 design criteria for building at the riverbank, while there are 14 design criteria for open space at the riverbank. These design criteria can enrich the warehouse district's revitalization by improving the visual quality of the urban environment.Keywords: design criteria; warehouse district; riverbank; Surabaya; revitalization.